AN ERROR ANALYSIS OF COHESION IN ENGLISH STUDENTS’ ESSAY WRITING AT STKIP YDB LUBUK ALUNG - Chandra, Julian (Dharmas Education Journal (DE_Journal), 2023)
One of the English academic writing at college is English essays. Since English essay writing is one skill that should be taught to students, English essays must be mastered by students. Although writing English essays is complete and well organized, it still has a big contribution to developing students’ writing ability. This research aims to describe the students’ errors of cohesion in students' English Essay writing at STKIP YDB Lubuk Alung. The samples of the research were students of the 3rd semester of the English Department of STKIP YDB Lubuk Alung using purposive sampling which consisted of eight students. The instrument of the research was documentation through students’ essay writing. This study explores types of cohesion that are classified into two cohesions, namely grammatical cohesion, and lexical cohesion. The grammatical cohesion involves references, substitutions, ellipses, and conjunctions. Meanwhile, lexical cohesion involves reiteration and colocation. The result of this study shows that there are 299 errors of cohesion in students’ essay writing. The errors found by grammatical cohesion are 203 and the errors of lexical cohesion are 96. Referring to the research findings, it is recommended that English writing lecturers should more attention to discussing, explaining, and analyzing all these errors to overcome the writing English essays problems dealing with grammatical cohesion and lexical cohesion.